The local limit theorem for the number of renewals - Nagaev, A. (Lithuanian Mathematical Journal, 1970)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: А. В. Нагаев. Локальная предельная теорема для числа восстановлений A. Nagajevas. Lokalinė ribinė teorema atstatymų skaičiui